Aloe vera and STS solution on microbial population and vase life of Heliconia cut flowers - Shokalu, Adekemi Olubukola; Israel, James; Mosunmola, Olatunji; Eniola, Oyedeji; Gift, Elum; Adebayo, Ajisafe; Henry, Akintoye (Ornamental Horticulture, 2021)
The use of several solutions as floral preservatives in extending the vase life of cut flowers has been an all-time research objective to meet the demands of florists and buyers. One of the major problems faced with the longevity of cut flowers is the accumulation of microorganism in the vase floral solution. This study was carried out to investigate the influence of Aloe vera gel and Silver thiosulphate solutions used as vase solution on the microbial population of Heliconia cut flowers. The experiment was carried out in the plant physiology laboratory, Floriculture programme, National Horticultural Research Institute, (NIHORT); Ibadan, Nigeria (7O25” N and 3O52” E). Six treatments supplemented with 1% sucrose were used in this experiment, they include; 1%, 2% and 4% Aloe vera gel solutions, 0.5% and 1% Silver thiosulphate solutions and distilled water (which serve as control) labeled AV1, AV2, AV3, STS1, STS2 and CO respectively. All treatments used for the vase life of Heliconia cut flowers were significantly (p ≤ 0.05) different in the parameters analyzed as compared to the control. The vase life, relative fresh weight and relative water content of Heliconia cut flowers were best with Aloe vera gel solutions compared to the control with AV3 recording the longest vase life of 12 days (58.21%). The microbial population in the vases of the cut flowers was greatly reduced with the application of the silver thiosulphate solutions (STS1 and STS2) compared with the control with STS2 recording the lowest microbial colony at 32.67 CFU mL-1. Promoting the use of organic floral preservatives should be encouraged as it is eco-friendly and cost effective. The result of the study reveals that the use of 4% Aloe vera solution has the potential to reduce microbial growth and also enhance the longevity of the cut flowers.